Penyegaran Wasit Sepak Bola Asprov Gorontalo Pada Persiapan Kompetisi Liga 4 - Gani, Ardin (Universitas Negeri Gorontalo, 2025)
This community service activity aimed to provide a refresher and improve the physical fitness and technical understanding of football referees under the Provincial Association (Asprov) of PSSI Gorontalo in preparation for the 2025 Liga 4 competition. The event was held on April 17, 2025, at the Sport Center Limboto and was attended by 21 referees. The refresher program focused on two main aspects: fitness evaluation through the interval test and speed capability through the 40-meter Sprint Ability Test. The results of the interval test indicated that 38.09% of participants were categorized as